2011
DOI: 10.1038/onc.2010.598
|View full text |Cite|
|
Sign up to set email alerts
|

Mitf is the key molecular switch between mouse or human melanoma initiating cells and their differentiated progeny

Abstract: In melanoma, as well as in other solid tumors, the cells within a given tumor exhibit strong morphological, functional and molecular heterogeneity that might reflect the existence of different cancer cell populations, among which are melanoma-initiating cells (MICs) with 'stemness' properties and their differentiated, fast-growing progeny. The existence of a slow-growing population might explain the resistance of melanoma to classical chemotherapies that target fast growing cells. Therefore, elucidating the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
233
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(258 citation statements)
references
References 27 publications
20
233
4
1
Order By: Relevance
“…39,42 Other epithelial-to-mesenchymal transition-regulatory transcription factors like SNAI1 and SNAI2 are not expressed in the FN1 high MITF low melanoma cells; SNAI1/2 are early epithelial-to-mesenchymal transition markers implicated in the initial induction of a migratory phenotype, whereas ZEB1 is an important regulator of the maintenance of this phenotype. 40,43 MITF was recently proposed as the transcriptional switch that drives stem-like melanoma cells toward differentiation, 29 which is in line with our hypothesis that FN1 high MITF low melanoma cells may represent a reservoir of slow-cycling stemlike/tumor-driving cells. Interestingly, hypoxia represses MITF expression and thereby enhances the metastatic potential of melanoma cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…39,42 Other epithelial-to-mesenchymal transition-regulatory transcription factors like SNAI1 and SNAI2 are not expressed in the FN1 high MITF low melanoma cells; SNAI1/2 are early epithelial-to-mesenchymal transition markers implicated in the initial induction of a migratory phenotype, whereas ZEB1 is an important regulator of the maintenance of this phenotype. 40,43 MITF was recently proposed as the transcriptional switch that drives stem-like melanoma cells toward differentiation, 29 which is in line with our hypothesis that FN1 high MITF low melanoma cells may represent a reservoir of slow-cycling stemlike/tumor-driving cells. Interestingly, hypoxia represses MITF expression and thereby enhances the metastatic potential of melanoma cells.…”
Section: Discussionsupporting
confidence: 71%
“…The ultrastructural features of high nucleocytoplasmic ratio, condensed heterochromatin and immature organelles (melanosomes and mitochondria) indicate a poorly differentiated status and suggest a link with stem-like melanoma cells. [26][27][28] This association is further supported by little or no expression of the melanocytic marker MITF 29 and the unique and high expression of FN1 indicative of an epithelial-to-mesenchymal transition-linked phenotype. 7 Furthermore, gene expression analysis of microdissected FN1 high melanoma cells revealed expression of other epithelial-to-mesenchymal transition (SNAI1 and ZEB1) and previously proposed stem-like melanoma cell markers (ABCB5, HIF2A, JARID1B, and NGFR).…”
Section: Discussionmentioning
confidence: 87%
“…It should be mentioned that several reports suggest that MITF might have an anti-melanoma activity. Indeed, MITF overexpression prevented xenograft tumour development (Carreira et al, 2006;Cheli et al, 2011). It was also reported that MITF upregulated the expression of two cyclin kinase inhibitors, CDKN2A (Loercher et al, 2005) and CDKN1A (Carreira et al, 2005), and MITF depletion was demonstrated to increase melanoma cell migration in vitro (Carreira et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But do the Mitf-low population truly exhibit stem-like properties? Cheli et al (2011) from Robert Ballotti's group in Nice now provide an answer. They show that short-term depletion of Mitf leads to an increase in expression of markers of stemness such as Oct4 and Nanog and that strikingly, although these cells were G1 arrested with high p27 and did not express other reported markers of melanoma stem cells such as ABCB5 or CD271, they nevertheless gave rise to larger allograft tumors.…”
mentioning
confidence: 99%